Characterization of phenology, physiology, morphology and biomass traits across a broad Euro‐Mediterranean ecotypic panel of the lignocellulosic feedstock Arundo donax. Issue 1 (16th September 2018) - Fabbrini, Francesco; Ludovisi, Riccardo; Alasia, Omar; Flexas, Jaume; Douthe, Cyril; Ribas Carbó, Miquel; Robson, Paul; Taylor, Gail; Scarascia‐Mugnozza, Giuseppe; Keurentjes, Joost J. B.; Harfouche, Antoine
Abstract: Giant reed ( Arundo donax L.) is a perennial rhizomatous grass, which has attracted great attention as a potential lignocellulosic feedstock for bioethanol production due to high biomass yield in marginal land areas, high polysaccharide content and low inhibitor levels in microbial fermentations. However, little is known about the trait variation that is available across a broad ecotypic panel of A. dona x nor the traits that contribute most significantly to yield and growth in drought prone environments. A collection of 82 ecotypes of A. donax sampled across the Mediterranean basin was planted in a common garden experimental field in Savigliano, Italy. We analysed the collection using 367 clumps representing replicate plantings of 82 ecotypes for variation in 21 traits important for biomass accumulation and to identify the particular set of ecotypes with the most promising potential for biomass production. We measured morpho‐physiological, phenological and biomass traits and analysed causal relationships between traits and productivity characteristics assessed at leaf and canopy levels. The results identified differences among the 82 ecotypes for all studied traits: those showing the highest level of variability included stomatal resistance, stem density (StN), stem dry mass (StDM) and total biomass production (TotDM). Multiple regression analysis revealed that leaf area index, StDM, StN, number of nodes per stem, stem height and diameter were the most significant predictors of TotDM and the most important early selection criteria for bioenergy production from A. donax . These traits were used in a hierarchical cluster analysis to identify groups of similar ecotypes, and a selection was made of promising ecotypes for multiyear and multisite testing for biomass production. Heritability estimates were significant for all traits. The potential of this ecotype collection as a resource for studies of germplasm diversity and for the analysis of traits underpinning high productivity of A. donax is highlighted. Abstract : A broad Euro‐Mediterranean panel of 82 ecotypes of giant reed ( Arundo donax L.) were phenotyped in a common garden experimental field in Italy. Twenty one morpho‐physiological, phenological and biomass traits were measured and causal relationships were analysed between traits and productivity characteristics at leaf and canopy levels. Multiple regression analysis revealed that leaf area index, stem dry mass, stem density, number of nodes per stem, stem height, and diameter were the most significant predictors of total biomass production and the most important early selection criteria for bioenergy production from A. donax .